Legal Protection of Educators in Non-Formal Education Institutions Given Law Number 13 of 2003 concerning Employment - Mofea, Sukhebi (PDPI (Perkumpulan Dosen Peneliti Indonesia), 2023)
This study aims to provide legal protection for educators in non-formal educational institutions. Protection of work agreements, rights and obligations, and social security for workers. Research method with survey approach. Data collection techniques were obtained from (1). Direct survey on research objects in the field (2). In-depth interviews with key sources (3). Documentation studies in the form of literature related to research. Data analysis and concluding by making descriptions in the form of sentences which can then be concluded. Result in that; (1) Legal protection for the parties to work agreements in non-formal institutions: it can be said that in employment relations the parties in non-formal educational institutions have not received legal protection and the parties should have agreed in writing so that they have legal force in carrying out their work. employment process following law no 13 of 2003 and the Civil Code. (2). Legal remedies that can be taken so that the parties in non-formal educational institutions receive legal protection is by means that the parties are aware of the work agreement contained in the articles of the work agreement starting from all employment mechanisms so that in the event of default in the future, each will have permanent legal force.